Assessment of OMI near‐UV aerosol optical depth over Central and East Asia. Issue 1 (14th January 2016) - Zhang, Wenhao; Gu, Xingfa; Xu, Hui; Yu, Tao; Zheng, Fengjie
Abstract: Several essential improvements have been made in recent Ozone Monitoring Instrument (OMI) near‐ultraviolet (UV) aerosol retrieval algorithm version (OMAERUV version 1.4.2), but few regional validations for its aerosol optical depth (AOD) product are conducted. This paper assessed the OMAERUV AOD product over Central and East Asia. The OMAERUV Level 2.0 AOD product was compared with Aerosol Robotic Network (AERONET) Level 2.0 direct Sun AOD measurement over 10 years (2005–2014) at 27 selected AERONET sites. A combined comparison of OMAERUV‐AERONET AOD at 25 (2) sites was carried out and yielded correlation coefficient ( ρ ) of 0.63 (0.77), slope of 0.53 (0.57), y intercept of 0.18 (0.13), and 50.71% (57.24%) OMAERUV AOD fall within the expected uncertainty boundary (larger by 0.1 or ±30%) at 380 nm (440 nm). The more accurate ( ρ > 0.70) OMAERUV retrievals are reported over eastern and northern China and South Korea. The two primary reasons for the underestimation of OMAERUV AOD over China are as follows: (1) the use of single‐channel (388 nm) retrieval method retrieves scattering AOD and not total AOD, and (2) the spectral dependence of the imaginary part of the refractive index in the near‐UV region assumed in the algorithm may not be representative of aerosols found over China. The comparisons for three predominant aerosol types indicate that smoke aerosol exhibits the best performance, followed by dust and nonabsorbing aerosol. It is consistent with the characteristic of near‐UV wavelength that it is more sensitive to absorbent particles. The comprehensive yearly (2005–2014) comparison at 25 sites and comparison between two periods (2005–2006 and 2009–2014) at selected four sites show no discernible decrease of temporal trend, which indicates that the OMAERUV algorithm successfully maintains its quality of aerosol product despite post‐2008 row anomaly instrument problem. Key Points: OMI AOD is assessed by AERONET direct Sun measurements over Central and East Asia Different aerosol types have distinct performance OMAERUV maintained its quality of aerosol product despite post‐2008 row anomaly instrument problem